Islands in the city : West Indian migration to New York - Foner, Nancy, 1945- (University of California Press, 2001)
This collection of original essays draws on a variety of theoretical perspectives, methodologies, and empirical data to explore the effects of West Indian migration and to develop analytic frameworks to examine it.